Environmental Status of Gandhisagar Reservoir - K.N., Kartha; K.S., Rao (Fishery Technology, 2025)
A study on the limnology, biota and productivity of Gandhisagar reservoir (Chambal river, Madhya Pradesh) was conducted. Gandhisagar reservoir was observed to have moderate nutrient concentrations oondudve to fish gowth. The qualitative abundance of planktonic population was high. The dominant phytoplankton, zooplankton, macrozoobenthos and microzoobenthos are presented in the text. Average primary productivity values for 12 months period were 40.83, 36.75 and 37.111 mgC /m3 /h respectively at surface, 2.5 m and 12 m depth